Financial innovation for climate justice: central banks and transformative `creative disruption' - Sokol, Martin (My University, 2023)
Global financial architectures, including central banks and their monetary policies, are critical to leveraging transformative change for climate justice. Yet, currently central banks are exacerbating rather than mitigating the climate crisis and climate injustices. By following a neoliberal policy paradigm and narrowly interpreted mandates for price stability and financial stability, central banks are focusing on stabilizing a system that is inherently unstable. This accelerates climate chaos around the world and is worsening future financial instability. Recognizing both the potential of central banks to advance climate justice and the inattention of the role of central banks in the climate crisis, this paper contributes to the emerging field of financial innovation for climate justice. First, we review what central banks are currently doing to advance and hinder climate justice. Then we explore monetary policy tools that central banks could deploy for transformative climate justice. We then make the case for ‘creative disruption’ in monetary policy which requires expanding the narrow mandate of central banks and new kinds of global coordination. This call for intentional creative disruption changes policy assumptions regarding financial stability and climate politics and reconceptualizes how to achieve transformative systemic change to move toward a more equitable, just, healthy, sustainable future.
PUBLISHED
Keywords: Financial innovation; Climate justice; Monetary policy; Central banks; Financialization; Creative disruption